Toxic Trauma A Basic Clinical Guide - Baker, David J. (Springer International Publishing : Imprint: Springer, 2016)
Winner of BMA Medical Book Award, Highly Commended in Public Health Written for medical professionals, this book provides a concise reference with clear guidelines on how to manage both the victims of chemical agent exposure and the site of the incident. David Baker considers the nature and basic science of the hazards faced as well as the practical management of persons exposed to chemicals and toxins.  Praise for the first edition "Toxic Trauma is a welcome addition to the literature. . . . Although written for clinicians, the book contains chapters that should be read by administrators and other health care professionals to ensure they understand and can inform the public in a balanced manner about the logistic considerations, and widespread consequences across systems when an event does occur. Any healthcare library should consider this book an essential text." --Michael Nurok, American Journal of Disaster Medicine "This book excels as a reference for those interested in learning about and designing systems to better handle toxic trauma." --Michael D. Zwank, Doody's Book Reviews.